2018
DOI: 10.3126/jnhrc.v16i1.19361
|View full text |Cite
|
Sign up to set email alerts
|

Universal Access to Essential Medicines: An Evaluation of Nepal’s Free Health Care Scheme

Abstract: Background: Access to medicine for the poor is recognized to be difficult task and one of the major challenges in achieving universal health coverage, particularly in low-and- middle income countries. In order to ensure the availability of essential medicines free of cost in public health facilities, Nepal has also commenced Free Health Care Services (FHCS). So, this study aims to evaluate availability, expiry, and stock-out duration of essential medicines at front line service providers in Nepal.Methods: Cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…However, availability and stock out of medicines in the studied villages of Annapurna region was comparable to other places of Nepal when compared to a study from Adhikari et al carried out in 2014 which reported 92.44% availability and 0.324 days of stock-out of medicines [15]. Study from Adhikari et al included both primary healthcare facilities and private drug retailers and was carried out in all three geographical region of Nepal the mountains, hills and plains while our study was carried out in the hills and mountain region only and did not included primary health care facilities and private drug retailers due to their absence in the studied villages [15]. This improvement could be due to both better logistics provision (better physical infrastructure of health facilities, good walking trails, access to porters and mules to carry goods and additional financial support from VDCs) in the Annapurna region because of sustainable tourism and local development initiatives, and improvement in the delivery of free basic healthcare services over the years since their inception in 2007 [8, 17].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, availability and stock out of medicines in the studied villages of Annapurna region was comparable to other places of Nepal when compared to a study from Adhikari et al carried out in 2014 which reported 92.44% availability and 0.324 days of stock-out of medicines [15]. Study from Adhikari et al included both primary healthcare facilities and private drug retailers and was carried out in all three geographical region of Nepal the mountains, hills and plains while our study was carried out in the hills and mountain region only and did not included primary health care facilities and private drug retailers due to their absence in the studied villages [15]. This improvement could be due to both better logistics provision (better physical infrastructure of health facilities, good walking trails, access to porters and mules to carry goods and additional financial support from VDCs) in the Annapurna region because of sustainable tourism and local development initiatives, and improvement in the delivery of free basic healthcare services over the years since their inception in 2007 [8, 17].…”
Section: Discussionsupporting
confidence: 70%
“…The overall state of access to medicines in the studied villages of the Annapurna region was good in comparison to a Nepalese study (2014) in Kathmandu, Banke and Bardia districts which reported 50–77% availability and 30% stock out of medicines, and international studies in Kenya (2009) with 46 days stock-out of medicines and in Jamaica (2010) with 90 days stock-out of medicines and unaffordable medicines prices [17–19]. However, availability and stock out of medicines in the studied villages of Annapurna region was comparable to other places of Nepal when compared to a study from Adhikari et al carried out in 2014 which reported 92.44% availability and 0.324 days of stock-out of medicines [15]. Study from Adhikari et al included both primary healthcare facilities and private drug retailers and was carried out in all three geographical region of Nepal the mountains, hills and plains while our study was carried out in the hills and mountain region only and did not included primary health care facilities and private drug retailers due to their absence in the studied villages [15].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The government of Nepal has been providing the essential medicines to government and public health facilities across the country even before the pandemic [ 45 ]. During the pandemic, the patients had timely access to life saving medicines for COVID-19 complications, as reflected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…interventions in countries such as Nepal [82,90], Ugunda [117,118] Rwanda [75], Tanzania [50,77], Ethiopia [119], Afghanistan [62] and…”
Section: Discussionmentioning
confidence: 99%